Virtualization of SCADA testbeds for cybersecurity research: A modular approach. Issue 77 (August 2018) - Alves, Thiago; Das, Rishabh; Werth, Aaron; Morris, Thomas
Highlights: Novel-modular framework is proposed to replicate critical infrastructure virtually. The proposed testbed is very low in cost and portable. Other testbeds are not fully portable and do not virtualize the controller. Success of this methodology is seen through case studies and cyberattacks. Abstract: SCADA systems were made robust to sustain tough industrial environments, but little care was taken to raise defenses against potential cyber threats. With time, the threats started pouring in and eliciting major concerns in the research community. The extremely high cost and critical nature of SCADA Systems has made it nearly impossible for researchers to perform experiments with live cyber-attacks. Hence, replicating the behavior of these complicated systems by developing high-fidelity testbeds and testing the vulnerabilities on them provides researchers with the necessary workspace to combat the threats currently haunting these legacy systems. However, high-fidelity testbeds like Deter and NSTB are not portable and are hard to replicate. Even though it was possible to identify some portable testbeds, they all have poor support on the virtualization of the SCADA controller or use hardware-in-the-loop, which affects portability. In this research, a novel-modular framework is proposed to replicate complex SCADA Systems entirely on a virtual simulation, which makes them very low cost and portable. The process of virtualizing each major component is discussed. Finally, the success of this methodology is demonstrated by replicating real world critical infrastructures, which are presented as case studies as well as cyberattacks to demonstrate the use of the framework for cybersecurity research.